2020
DOI: 10.1080/09544828.2020.1851662
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mixed reality implementation on early-stage interactive product design process

Abstract: This article proposes a novel approach towards quick concept generation and validation of interactive-product behaviours. When designing for user-product interactions, designers have to consider spatial and behavioural elements besides form/tangible aspects and perform quick-validation of the generated concepts often done through functional prototyping at later design stages. As a result, the designed-outcomes often depend on parameters like designer's familiarity with the design tools used, the level of fidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In terms of validity for shape ideation, the paper validates the findings Oti and Crilly (Oti and Crilly, 2020) on early stage designing with VR. In terms of personal effectiveness and enjoyment these findings confirm those of Özgen et al and Maurya et al (Maurya et al, 2020;Özgen et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In terms of validity for shape ideation, the paper validates the findings Oti and Crilly (Oti and Crilly, 2020) on early stage designing with VR. In terms of personal effectiveness and enjoyment these findings confirm those of Özgen et al and Maurya et al (Maurya et al, 2020;Özgen et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…XR technologies enable to construct and display immersive environments for a wide range of applications, from medical treatment (Andrews et al, 2019), through manufacturing (Juraschek et al, 2018) and up to research into human cognition (Clay, König and König, 2003). Expectedly, they are being explored by design researchers as well (Maurya, Mougenot and Takeda, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Park et al [16] demonstrated design evaluations of digital consumer products using virtual reality-based functional behavior simulation. As the interaction with the virtual interface does not invalidate the usability evaluation itself [17], VR tests can be used widely and have exerted a huge impact on early-stage interactive product design processes [18]. However, it is not only for virtual products that evaluation in VR offers advantages.…”
Section: Testing In Vrmentioning
confidence: 99%